Perancangan Tama Boutique Hotel Dengan Pendekatan Brand Identity - Maqdis Auliah Suhendi, Khodijah; Laksitarini, Niken; Bayu Perdana, Aditya (eProceedings of Art & Design, 2024)
Bandung is one of the major cities on the island of Java, which has many interesting tourist attractions to visit. In accommodating foreign and domestic tourists, overnight facilities are needed, one of which is a hotel. With the increase in the number of tourists to the city of Bandung, one of them is a boutique hotel. One of the boutique hotels in the city of Bandung is Tama Boutique Hotel, which is more precisely located on Jl. Dr. Boutique hotels have an attraction for tourists, namely the strength of uniqueness, identity, and strong character in hotel style or design. This analysis aims as a reference or learning in applying concepts to the interior design of the Boutique Hotel. The data collection method is based on direct surveys and the data obtained is analyzed for the application of concepts from the surrounding elements and materials used in accordance with the intended concept theme. This design aims to create a 4-star boutique hotel with more prominent characteristics and branding by displaying new concept themes and facilities that provide new experiences, and comfort to visitors. Keywords: boutique hotel, brand identity, Tama Boutique Hotel